Questions of modernity - Mitchell, Timothy, 1955- (Minneapolis : University of Minnesota Press, 2000)
Modernity has always laid claim to universal certainty--which meant assigning a different and lesser significance to anything deemed purely local, non-Western, or lacking a universal expression. Focusing on the making of modernity outside the West, eight leading anthropologists, historians, and political theorists explore the production of new forms of politics, sensibility, temporality, and selfhood in locations ranging from nineteenth-century Bengal to contemporary Morocco.
Stage of modernity / Timothy Mitchell -- Two poets and death : on civil and political society in the non-Christian world / Partha Chatterjee -- Witness to suffering : domestic cruelty and the birth of the modern subject in Bengal / Dipesh Chakrabarty -- Modern subjects : Egyptian melodrama and postcolonial difference / Lila Abu-Lughod -- Thin line of modernity : some Moroccan debates / Stefania Pandolfo -- Sovereignty of history : culture and modernity in the cinema of Satyajit Ray / Nicholas B. Dirks -- Making of modernity : gender and time in Indian cinema / Veena Das -- Body politic in colonial India / Gyan Prakash.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Developing countries -- Social conditions; Civilization, Modern; Developing countries -- Politics and government; Civilisation moderne et contemporaine; Pays en voie de développement -- Conditions sociales; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Civilization, Modern; Politics and government; Social conditions; Developing countries